2019
DOI: 10.1038/s41586-019-1676-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of strontium in the merger of two neutron stars

Abstract: Half of all the elements in the universe heavier than iron were created by rapid neutron capture. The theory for this astrophysical 'r-process' was worked out six decades ago and requires an enormous neutron flux to make the bulk of these elements. 1 Where this happens is still debated. 2 A key piece of missing evidence is the identification of freshly-synthesised r-process elements in an astrophysical site. Current models 3-5 and circumstantial evidence 6 point to neutron star mergers as a probable r-process … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
345
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(385 citation statements)
references
References 48 publications
35
345
2
3
Order By: Relevance
“…The delayed r-process source is most likely neutron star mergers (NSMs) since they are confirmed r-process sites (e.g. Watson et al 2019). The estimated time delay of the event GW170817, which is currently the only directly observed NSM with a confirmed host galaxy (Pan et al 2017;Blanchard et al 2017), is in good agreement with our timescale of t delayed 4 Gyr.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed r-process source is most likely neutron star mergers (NSMs) since they are confirmed r-process sites (e.g. Watson et al 2019). The estimated time delay of the event GW170817, which is currently the only directly observed NSM with a confirmed host galaxy (Pan et al 2017;Blanchard et al 2017), is in good agreement with our timescale of t delayed 4 Gyr.…”
Section: Discussionmentioning
confidence: 99%
“…J π n s S 0 4 9/2 + 1g 9/2 0.82 (13) 1195 (20) (2) (5/2 + ) (2d 5/2 ) a 0.47 (9) 1600 (45) (2) (5/2 + ) (2d 5/2 ) a 0.13 (2) 1810 (20) (2) (5/2 + ) (2d 5/2 ) a 0.42 (7) 1960(30) (0) (1/2 + ) (3s 1/2 ) ≡ 1.00 2335 (20) (2) (3/2 + ) (2d 3/2 ) 1.00 (17) 2530 (20) (4) (7/2 + ) (1g 7/2 ) 0.62 (12) a The centroid of the 2d 5/2 strength lies at 1500(50) keV, with C 2 S = 1.02 (17).…”
Section: E (Kev)mentioning
confidence: 99%
“…The robustness of the N = 126 neutron shell closure plays a crucial role in the nucleosynthesis of the actinides [3][4][5][6][7]. The recent observation of a neutron star merger has provided a new focus of interest [8,9], suggesting a possible astrophysical environment for r-process nucleosynthesis [10-13].Approaching the r-process path along the N = 126 isotonic chain from Pb, the binding energies (the degree to which neutrons are bound by the mean-field potential created by the decreasing number of all other nucleons) decrease, eventually crossing zero binding and becoming unbound. Near closed shells, the level density is low, so the usual statistical assumptions of many resonances participating in neutron capture is not valid, and specific nuclear-structure properties become important.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many remarkable results in astrophysics and in fundamental physics have already been obtained thanks to these first detections. To mention only a few highlights, the observation of the NS-NS binary coalescence GW170817 solved the long-standing problem of the origin of (at least some) short gamma ray bursts [2,10,11]; the multi-band observations of the associated kilonova revealed that NS-NS mergers are a site for the formation of some of the heaviest elements through r-process nucleosynthesis [12][13][14][15]; the observation of tens of BH-BH coalescences has revealed a previously unknown population of stellar-mass BHs, much heavier than those detected through the observation of X-ray binaries [16], and has shown that BH-BH binaries exist, and coalesce within a Hubble time at a detectable rate. Concerning fundamental physics, cosmology and General Relativity (GR), the observation of the GWs and the gamma-ray burst from the NS-NS binary GW170817 proved that the speed of GWs is the same as the speed of light to about a part in 10 15 [5]; the GW signal, together with the electromagnetic determination of the redshift of the source, provided the first measurement of the Hubble constant with GWs [17]; the tail of the waveform of the first observed event, GW150914, showed oscillations consistent with the prediction from General Relativity for the quasi-normal modes of the final BH [18]; several possible deviations from GR (graviton mass, post-Newtonian coefficients, modified dispersion relations, etc.)…”
mentioning
confidence: 99%